2019
DOI: 10.1080/21645515.2019.1593082
|View full text |Cite
|
Sign up to set email alerts
|

A review of complement sources used in serum bactericidal assays for evaluating immune responses to meningococcal ACWY conjugate vaccines

Abstract: Invasive meningococcal disease is rare and potentially devastating but often vaccine-preventable. Evaluation of meningococcal vaccine effectiveness is impractical owing to relatively low disease incidence; protection is therefore estimated using serum bactericidal antibody (SBA) assays. Original experiments on natural immunity established a titer of ≥4 as the correlate of protection for SBA assays using human complement (hSBA), but human complement is relatively difficult to obtain and standardize. Use of baby… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 71 publications
1
31
0
Order By: Relevance
“…21 Both SBA assays and GMTs were used due to differing preferences globally for licensing data; the first MCV4 was licensed by the US Food and Drug Administration in 2005 based on rSBA assay data, 16,22 however, in Europe, MCV4-CRM was licensed in 2009 on the basis of hSBA assay data, with some rSBA assay data in the assessment report, 16,23 whilst MCV4-TT in 2012 relied primarily on rSBA assay results, with some hSBA assay data. 16,24 All participants in both groups had seroprotective levels of tetanus toxoid antibody concentrations at baseline. Anti-tetanus antibody GMCs increased in both vaccine groups, albeit with numerically higher responses in the MenACYW-TT group, consistent with a higher tetanus toxoid concentration in this vaccine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Both SBA assays and GMTs were used due to differing preferences globally for licensing data; the first MCV4 was licensed by the US Food and Drug Administration in 2005 based on rSBA assay data, 16,22 however, in Europe, MCV4-CRM was licensed in 2009 on the basis of hSBA assay data, with some rSBA assay data in the assessment report, 16,23 whilst MCV4-TT in 2012 relied primarily on rSBA assay results, with some hSBA assay data. 16,24 All participants in both groups had seroprotective levels of tetanus toxoid antibody concentrations at baseline. Anti-tetanus antibody GMCs increased in both vaccine groups, albeit with numerically higher responses in the MenACYW-TT group, consistent with a higher tetanus toxoid concentration in this vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…This Phase II study was conducted to evaluate the immunogenicity and safety of MenACYW-TT compared with the licensed vaccine MCV4-TT, in healthy toddlers, using both human complement (hSBA) and baby rabbit complement (rSBA) serum bactericidal antibody assays. hSBA titers ≥4 are an accepted surrogate of protection against serogroups A and C. 15 However, assays using rSBA complement have been used as the basis for licensure of most meningococcal vaccines, with data supporting the acceptance of rSBA titers ≥8 as the correlate of protection against serogroup C. 16…”
Section: Introductionmentioning
confidence: 99%
“…Meningococcal factor H binding protein may help to explain the difference [21,22]. Factor H binding protein prevents complement-mediated killing [23].…”
Section: Surrogates Of Protectionmentioning
confidence: 99%
“…A series of studies observed that the hSBA but not rSBA titers decreased rapidly post-vaccination, especially serogroup A [24][25][26][27], suggesting that hSBA may underestimate immune response to MenACWY-TT [23]. hSBA assays may also suggest lower initial immune response to serogroup W and Y than rSBA assays, especially for toddlers receiving one dose of vaccine [23,[26][27][28]. However, hSBA titers increased at later time points despite no additional booster doses.…”
Section: Surrogates Of Protectionmentioning
confidence: 99%
See 1 more Smart Citation